Effects of a School-Based Sports Program on Physical Fitness, Physical Activity, and Cardiometabolic Health in Youth With Physical Disabilities: Data From the Sport-2-Stay-Fit Study - Zwinkels, Maremka; Verschuren, Olaf; Balemans, Astrid; Lankhorst, Kristel; te Velde, Saskia; van Gaalen, Leendert; de Groot, Janke; Visser-Meily, Anne; Takken, Tim (Frontiers in Pediatrics, 2018)
Objective To investigate the effects of a school-based once a week sports program on physical fitness, physical activity, and cardiometabolic health in children and adolescents with a physical disability. Methods This controlled clinical trial included 71 children and adolescents from four schools for special education (mean age 13.7 (2.9) years, range 8-19, 55% boys). Participants had various chronic health conditions including cerebral palsy (37%), other neuromuscular (44%), metabolic (8%), musculoskeletal (7%), and cardiovascular (4%) disorders. Before recruitment and based on the presence of school-based sports, schools were assigned as sport or control group. School-based sports was initiated and provided by motivated experienced physical educators. The sport group (n=31) participated in a once a week school-based sports program for six months, which included team sports. The control group (n=40) followed the regular curriculum. Anaerobic performance was assessed by the Muscle Power Sprint Test. Secondary outcome measures included aerobic performance, VO2peak, strength, physical activity, blood pressure, arterial stiffness, body composition and the metabolic profile. Results A significant improvement of 16% in favour of the sport group was found for anaerobic performance (p=.003). In addition, the sport group lost 2.8% more fat mass compared to the control group (p=.007). No changes were found for aerobic performance, VO2peak, physical activity, blood pressure, arterial stiffness, and the metabolic profile. Conclusions Anaerobic performance and fat mass improved following a school-based sports program. These effects are promising for long-term fitness and health promotion, because sports sessions at school eliminate certain barriers for sports participation and adding a once a week sports session showed already positive effects over six months. This trial was registered with the Dutch Trial Registry (NTR4698)